Game demands of seven-a-side soccer in young players - Barbero-Alvarez, J. C.; Gómez-López, M.; Castagna, C.; Barbero-Alvarez, V.; Romero, D. V.; Blanchfield, A. W.; Nakamura, F. Y. (The Journal of Strength and Conditioning Research, 2017)
The aim of this study was to examine the activity patterns and physiological demands of 7-a-side youth soccer matches across 2 chronological age categories (U12 and U14). Twenty-two soccer players of a national youth soccer academy were investigated. Players of each age category performed 2 training matches (2 × 25 minutes) and were monitored by global positioning system and heart rate monitor units. Players of both categories covered similar total distance (5,348 ± 307 m), at similar mean heart rate values (86 ± 4% of maximum). However, the number of high-intensity runs (82.5 ± 17.4 vs. 69.7 ± 15.2) and total distance covered during sprints (264 ± 207 vs. 128 ± 74 m) were significantly (p = 0.05) higher in U14 compared with U12. The results suggest a highly demanding nature of 7-a-side soccer for skilled players, with physical maturity possibly influencing the match-related high-intensity performance at these ages.